2019
DOI: 10.5505/ejm.2019.02486
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between change in respiratory muscle strength and cough ability in patients submitted to open-heart surgery

Abstract: The purpose of this study was to determine the correlation between change in respiratory muscle strength and change in cough ability in patients submitted to open-heart surgery. An observational cross-sectional study was conducted among 52 participants. Respiratory muscle strength was assessed by maximal inspiratory pressure (MIP) and maximal expiratory pressure (MEP) using a respiratory pressure meter. Cough ability was evaluated by voluntary expiratory peak flow (PEF) using a digital spirometer. Evaluations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Regarding postoperative angle change, the study also discovered a significant reduction in maximal inspiratory pressure in the postoperative period. The decrease in respiratory muscle strength is associated with intraoperative factors (eg, type of surgery, general anesthesia, medication of heart, cardiovascular bypass, and ventilator use) and postoperative pain [ 11 ]. Injury of the phrenic nerve, which is the main breathing muscle, can occur during cardiac surgery because of the position of the phrenic nerve running from the neck to the upper thorax through the mediastinum to the parietal pleura and fibrous pericardium [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding postoperative angle change, the study also discovered a significant reduction in maximal inspiratory pressure in the postoperative period. The decrease in respiratory muscle strength is associated with intraoperative factors (eg, type of surgery, general anesthesia, medication of heart, cardiovascular bypass, and ventilator use) and postoperative pain [ 11 ]. Injury of the phrenic nerve, which is the main breathing muscle, can occur during cardiac surgery because of the position of the phrenic nerve running from the neck to the upper thorax through the mediastinum to the parietal pleura and fibrous pericardium [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these might be the cause of long-term musculoskeletal and respiratory problems that interfere with the patient’s daily life. Furthermore, several studies have reported changes in patients’ respiratory muscle strength when comparing before and after heart surgery [ 10 , 11 ]. Measuring maximal inspiratory pressure is a simple way of determining inspiratory muscle strength [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%